Multidirectional UV-LED lithography using an array of high-intensity UV-LEDs and tilt-rotational sample holder for 3-D microfabrication - Sabera Fahmida Shiba (Micro and Nano Systems Letters, 2020)
Abstract This paper presents a computer-controlled multidirectional UV-LED lithography system for 3-D microfabrication. The presented UV-LED system has adopted adjustable or programmable high-intensity UV-LEDs as a light source enabling for photopatterning both thin and thick SU-8 photoresist process. The prototype of the proposed system comprises 5-by-5 surface-mounted type LEDs with customized collimation lens, a tilt-rotational sample holder for introducing multidirectional light exposure, and a computer-control asset for synchronized controls of the light source and the sample holder. An adjustable light intensity provides an ease of lithography both for a few micron feature size patterning and a millimeter thick photopatterning by providing optimal light exposure condition by considering diffraction, and absorption of the UV light. Together with the tilt-rotational sample holder, the multidirectional UV-LED lithography can fabricate various 3-D microstructures in a wide range of the photoresist film thickness. The 3-D fabrications include an array of micro triangle slabs, 1-mm tall pillar array, the different scale same 3-D geometry structures on the same substrate.